Nonviolent coexistence : moving communities beyond fear, suspicion, and the weapons of war - Rupesinghe, Kumar; Fernando, Gayathri; Foundation for Co-Existence (Colombo, Sri Lanka) (Maharagama : Foundation for Co-Existence, Sri Lanka, 2007)
Contributed articles.
Keywords: Nonviolence; Coexistence